2018
DOI: 10.1002/cam4.1590
|View full text |Cite
|
Sign up to set email alerts
|

How great is current curative expenditure and catastrophic health expenditure among patients with cancer in China? A research based on “System of Health Account 2011”

Abstract: In recent years, the incidence and mortality of cancer have witnessed a dramatic increase. Cancer has already caused severe economic burdens on society, especially in developing countries and has become a major public health concern. This study evaluates the medical economic burden, including total current curative expenditure (CCE) and catastrophic health expenditure (CHE) on cancer in Liaoning Province, China. A total of 252 medical institutions were investigated with multistage stratified cluster random sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 16 publications
3
50
1
Order By: Relevance
“…Cancer cost was predominant in people aged from 50 to 70. This supports existing evidence in China and consistent with epidemiological findings that most cancer incidence rates increase exponentially with aging . As for the expenditure pattern, we found that cost attributed to medication accounted a large proportion in both inpatient (37.7%) and outpatient care (64.6%) across all kinds of cancers.…”
Section: Discussionsupporting
confidence: 90%
“…Cancer cost was predominant in people aged from 50 to 70. This supports existing evidence in China and consistent with epidemiological findings that most cancer incidence rates increase exponentially with aging . As for the expenditure pattern, we found that cost attributed to medication accounted a large proportion in both inpatient (37.7%) and outpatient care (64.6%) across all kinds of cancers.…”
Section: Discussionsupporting
confidence: 90%
“…This proportion was similar to a recent study conducted, where the authors found the incidence of CHE for six types of cancers including esophageal, colon, gastric, liver, lung, and breast cancer to be 42.78%. 20 The prevalence of CHE was also similarly reported in prior studies conducted in Malaysia (47.8%), 24 South Korea (39.8%), 15 and eight Southeast Asian countries (48%). 19 However, this proportion was much lower than in another study conducted in China.…”
Section: Discussionsupporting
confidence: 75%
“…In addition, the threshold used to define CHE varied across the studies, ranging from 10%, 15 30% 19 and 40%. 20,21,24 In light of the possible shortcomings in previous studies, non-medical expenses and other sources of compensation, such as charity assistance, were included in the calculation of CHE in the current study. Nonetheless, results from both the current study and previous studies indicate that there is a potential risk for leukemia to result in significant financial and economic burden.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A reasonable health nancing system should focus on public nancings such as government and social medical insurance, and control the personal cash health expenditure (OOP) paid by the family to a lower level [17]. If the health nancing system relies too much on household health expenditures, it will easily lead to catastrophic expenditure or poverty due to illness [18]. Due to physical reasons, children's resistance is poor and they are more likely to get sick, which not only leads to the loss of children's health but also brings a huge cost of disease treatment.…”
Section: Discussionmentioning
confidence: 99%